Asolectin from soybeans as a natural compatibilizer for cellulose‐reinforced biocomposites from tung oil. Issue 17 (14th January 2015) - Johns, Ashley; Morris, Steven; Edwards, Kyle; Quirino, Rafael Lopes
ABSTRACT The free radical copolymerization of tung oil, divinylbenzene, and n‐butyl methacrylate results in bio‐based thermosetting polymers with tunable properties. Biocomposites have been obtained by the reinforcement of such bio‐based resins with α‐cellulose. Asolectin from soybeans consists of a mixture of natural, polyunsaturated phospholipids. Because of its long, unsaturated fatty acid chains, and the presence of phosphate and ammonium groups, asolectin from soybeans is a good candidate for acting as a natural compatibilizer between the hydrophobic matrix and the hydrophilic reinforcement. In the current work, we investigate the changes in properties resulting from the addition of asolectin to a tung oil‐based polymer reinforced with α‐cellulose. An evaluation of the cure‐kinetics of the tung oil‐based resin has been conducted by dielectric analysis (DEA), and the final biocomposites have been thoroughly characterized by differential scanning calorimetry (DSC), thermogravimetric analysis (TGA), dynamic mechanical analysis (DMA), Soxhlet extraction, and scanning electron microscopy (SEM). © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 41833.